FORMULASI DAN EVALUASI FISIK KRIM KOSMETIK DENGAN VARIASI EKSTRAK KAYU SECANG (Caesalpinia sappan) DAN BEESWAX SUMBAWA - Nealma, Samuyus; Nurkholis (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
In this research, secang wood will be used as a cream using Sumbawa beeswax base. The purpose of this study was to obtain the best cream formulation with secang wood extract and beeswax. Cream formula is based on the concentration of secang extract 0.5-2.5 grams and beeswax 0.2-4 grams in 20 grams of the preparation. Determination of physical evaluation will be carried out several tests, namely organoleptic test, pH, adhesion, dispersal power and protective power. The results showed that all three formulas, Formulation 1 (F1) and F3 were homogeneous, while F2 was not homogeneous. In pH testing, all formulations 1,2 and 3 have an average pH of 6. And in organoleptic testing, F3 shows a score of 3.9 in form and is the highest compared to the two other formulations, F1 has a score of 2.8, F2 scores 2.2. Whereas in color organoleptic, the highest score is F3 with a score of 3.8, F1 score 2.8 and F3 score 2.2. And in odorless organoleptics, F1 has the highest score of 3.6, F3 score of 3.3 and F2 score of 2.7. In the scatter power test, F1 has an average value of 11.8, F2 with a value of 53.52 and F3 with a value of 11.68. F1, F2 and F3 adhesion tests have values ??of 2.3 seconds, 2.3 and 3.67, respectively. And in KOH protection testing all formulas show changes.